Dialogic Failure and Decolonial Resistance: A Bakhtinian Reading of Things Fall Apart (Revue El-Wahat pour les Recherches et les Etudes, 2026)
This article offers a literary-sociocultural approach in reading Chinua Achebe’s Things Fall Apart,  using Mikhail Bakhtin’s theory of dialogism to frame failure in the novel as dialogic and a site of decolonial resistance. Through dialogism, heteroglossia, and cyclical temporality, this study  shows how Igbo society mediates justice, knowledge, and communal life through negotiation and collective accountability. Okonkwo’s monologic rigidity mirrors the monologic frameworks of coloniality, contrasting with the dialogic ethos of Igbo society and revealing how colonial disruption threatens communal negotiation, indigenous knowledge and temporalities. Failure emerges as a method of preserving indigenous temporalities, moral reasoning, and oral traditions, asserting the validity of alternative ways of knowing, and challenging Western linear, monologic frameworks.